Psychological health and its main criteria - Sadiqova Gulbarno; Umarkulova Madina (Euro Asian Journal Publishing, 2024)
Thoughts on psychological health and its basic criteria have seen on emotional views, the concept of scientific health, emotional, stable, and unstable emable.
Keywords: psychology; immovosity; health